USM AND GRI-DU TO SHARE EXPERTISE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 7 December 2016 – Universiti Sains Malaysia (USM) through the Knowledge Transfer Programme (KTP) is sharing its expertise in various fields, especially in science with Gandhigram Rural Institute Deemed University (GRIDU), India.